AVALIAÇÃO DO VALOR NUTRITIVO DE BAGAÇO DE CANA-DE-AÇÚCAR TRATADO BIOLOGICAMENTE - d’Arce, R. D.; Machado, P. F.; Mattos, W. R. S.; Castro, F. B.; Coutinho, L. L.; d’Arce, R. J. M. (REVISTA DE AGRICULTURA, 2015)
AVALIAÇÃO DO VALOR NUTRITIVO DE BAGAÇO DE CANA-DE-AÇÚCAR TRATADO BIOLOGICAMENTE